The devil is in the data: differences in drug persistence between SNIIRAM, the French national health insurance database, and psoriasis biologics intervention registers. (2nd January 2019) - Grantham, Henry J.; Reynolds, Nick J.
Abstract : Linked Article:  Sbidian et al. Br J Dermatol 2019;180 :86‐93 .